2023
DOI: 10.1371/journal.pone.0294282
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of aging-related genes in atrial fibrillation

Yong Zhou,
Chao Sun,
Yingxu Ma
et al.

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia in the clinic. Aging plays an essential role in the occurrence and development of AF. Herein, we aimed to identify the aging-related genes associated with AF using bioinformatics analysis. Transcriptome profiles of AF were obtained from the GEO database. Differential expression analysis was performed to identify AF-specific aging-related genes. GO and KEGG enrichment analyses were performed. Subsequently, the LASSO, SVM-RFE, and MCC algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Wu et al ( 82 ) found that CD8+ T cells were significantly more prevalent in AF patients than in individuals with normal rhythm. Zhou et al ( 83 ) observed that macrophage M2, activated NK cells, and neutrophils might be implicated in the pathogenesis of AF. Our findings indicate an increased expression of plasma cells and NK cells in AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al ( 82 ) found that CD8+ T cells were significantly more prevalent in AF patients than in individuals with normal rhythm. Zhou et al ( 83 ) observed that macrophage M2, activated NK cells, and neutrophils might be implicated in the pathogenesis of AF. Our findings indicate an increased expression of plasma cells and NK cells in AF patients.…”
Section: Discussionmentioning
confidence: 99%